Correction to: A binding-block ion selective mechanism revealed by a Na/K selective channel - Jie Yu; Bing Zhang; Yixiao Zhang; Cong-qiao Xu; Wei Zhuo; Jingpeng Ge; Jun Li; Ning Gao; Yang Li; Maojun Yang (Protein & Cell, 2019)
In the original publication the PDB numbers were not cited.